2023
DOI: 10.1007/s42773-023-00244-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochar application in remediating salt-affected soil to achieve carbon neutrality and abate climate change

Abstract: Salt-affected soils urgently need to be remediated to achieve the goals of carbon neutrality and food security. Limited reviews are available on biochar performance in remediating salt-affected soils in the context of carbon neutrality and climate change mitigation. This work summarized the two pathways to achieve carbon neutrality during remediating salt-affected soils using biochars, i.e., biochar production from sustainable feedstock using thermal technologies, application for promoting plant productivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 179 publications
0
8
0
Order By: Relevance
“…We can infer from a comparison of research ndings that various quality and feedstock biochar have distinct effects on heavy metal levels in soil. Furthermore, biochar can be one of the strategies to combat with salt-affected soil (Liu et al 2023). It is con rmed by another study, reported that adding biochar to salt-affected soils improves their chemical, biological, and physical characteristics(Dahlawi et al 2018).…”
Section: The Potential Impacts Of Cmb On Contaminated Agricultural Soilmentioning
confidence: 95%
“…We can infer from a comparison of research ndings that various quality and feedstock biochar have distinct effects on heavy metal levels in soil. Furthermore, biochar can be one of the strategies to combat with salt-affected soil (Liu et al 2023). It is con rmed by another study, reported that adding biochar to salt-affected soils improves their chemical, biological, and physical characteristics(Dahlawi et al 2018).…”
Section: The Potential Impacts Of Cmb On Contaminated Agricultural Soilmentioning
confidence: 95%
“…The sorption capabilities of biochar present opportunities for soil remediation, with potential applications in mitigating pollutants [68]. The positive effects observed in soil properties, such as porosity, bulk density, water dynamics, acidification, interplay with soil organic matter, attenuation of priming effects, and induction of soil microbial activity, contribute to its overall positive impact [66].…”
Section: The Cascaded Use Of Biochar Prior To Its Permanent Storage I...mentioning
confidence: 99%
“…Although they are unlikely to replace well-characterized, reproducible and highly stable chemical catalysts, including plasma catalysts, they are seen as an important renewable material in climate change mitigation, especially in agriculture as a soil additive [177] as well as in numerous other applications [171,178]. Therefore, biochars can be used in applications such as the present one in which they act as catalysts and at the same time they are chemically modified to be more effective soil conditioners.…”
Section: Biochar As Plasma Catalyst and Oxygen Scavengermentioning
confidence: 99%